Procreauto: costos e inflación - Andonian, Olga Graciela; Rópolo, Mariela Soraya; Rabbia, Evelín Mariel (2022)
Fil: Andonian, Olga Graciela. Universidad Nacional de Córdoba. Facultad de Ciencias Económicas; Argentina.